Increasing Staphylococcus Species Resistance in Peritoneal Dialysis-Related Peritonitis Over a 10-Year Period in a Single Taiwanese Center. Issue 4 (July 2018) - Chen, Ho-Ching; Shieh, Chi-Chang; Sung, Junne-Ming
Background: Peritonitis is a major complication of peritoneal dialysis (PD). Staphylococcus species are gram-positive bacteria that are most commonly associated with peritoneal peritonitis. The increasing antimicrobial resistance rate is a severe burden when considering the initial choice of antibiotics. This investigation examined the trends of staphylococcal infection as well as the resistance rate and clinical outcomes from 2006 to 2015 in southern Taiwan. Methods: We retrospectively investigated all PD-related peritonitis episodes in southern Taiwan between January 2006 and December 2015 and evaluated the clinical characteristics of peritonitis, microbiological prevalence and resistance of Staphylococcus species, and outcomes in patients. Results: Among 244 episodes of peritonitis, Staphylococcus species accounted for approximately 65% of the gram-positive bacteria that caused the infection. The methicillin resistance rate among Staphylococcus species substantially increased to 64% by 2015 in both Staphylococcus aureus and coagulase-negative staphylococci in southern Taiwan. Notably, patients with methicillin-resistant staphylococcal infection exhibited a significantly higher hospitalization rate than those with methicillin-sensitive staphylococcal infection. However, the catheter removal rate and transfer to hemodialysis exhibited no differences between the 2 groups. Conclusion: Peritonitis is the most serious complication in patients on PD, and microbiological trends have changed over the past 10 years at a single center in southern Taiwan. The number of methicillin-resistant Staphylococcus species has substantially increased. Empirical initial antibiotic therapy should be adapted on the basis of the growing microbiological resistance.